Perceptions of an open visitation policy by intensive care unit workers - Fernando da Silva Ramos; Renata Rego Lins Fumis; Luciano César Pontes Azevedo; Guilherme Schettino (2013)
An intensive care unit (ICU) admission is a stressful event for the patient and the patient's family. Several studies demonstrated symptoms of anxiety, depression, and posttraumatic stress disorder in family members of patients admitted to ICU. Some studies recognize that the open visitation policy (OVP) is related to a reduction in symptoms of anxiety and depression for the patient and an improvement in family satisfaction. However, some issues have been presented as barriers for the adoption of that strategy. This study was designed to evaluate perceptions of physicians, nurses, and respiratory therapists (RTs) of an OVP and to quantify visiting times in a Brazilian private intensive care unit (ICU). This observational and descriptive study was performed in the medical-surgical (22 beds) and neurologic ICU (8 beds) of Sírio-Libanês Hospital (HSL), São Paulo, Brazil. All physicians, nurses, and RTs from ICU were invited to participate in the study. A questionnaire was applied to all ICU workers who accepted to participate in the study. The questionnaire consisted of 22 questions about the visiting policy. During five consecutive days, we evaluated the time that the visitors stayed in the patient room, as well as the type of visitor. A total of 106 ICU workers participated in this study (42 physicians, 39 nurses, and 25 RTs). Only three of the questions exposed a negative perception of the visiting policy: 53.3% of the participants do not think that the OVP consistently increases family satisfaction with patient's care; 59.4% of ICU workers think that the OVP impairs the organization of the patient's care; 72.7% of participants believe that their work suffers more interruptions because of the OVP. The median visiting time per day was 11.5 hours. According to physicians, nurses, and respiratory therapists, the greatest impact of OVP is the benefit to the patients rather than to the family or to the staff. Furthermore, they feel that they need communication training to better interact with family members who are present in the ICU 24 hours per day.